(untitled) (AYUSHDHARA, 2023)
Functional neurological symptom disorder (FND)/Conversion disorder may be broadly defined as the presence of neurologic symptoms in the absence of a neurologic diagnosis, or when a neurologic diagnosis exists, it does not fully account for all of the patient’s symptoms. The cardinal symptom is limited solely to neurological symptoms. The diagnosis is made on the basis of the positive findings of the examination demonstrating preserved neurological function. Yoshapasmara, described in Madhava nidana, is comparable to FND where gathi / samvedhana (motor or sensory functions) are lost in the absence of underlying neurological conditions. A 29-year female was admitted with C/o Weakness and numbness in the left lower limb for 6 months. She had severe stress factors due to family conflicts. One day after a conflict with her mother-in-law, she felt difficulty walking on her left leg. They consulted a neurologist and done imaging, which was normal. On detailed clinical examination, the diagnosis was FND. She was managed with Internal medications and Udwartana, Abyanga, and Vyathyasa chikitsa (Dry and unctuous therapies alternatively). Hypnotherapy was administered in addition to Ayurvedic management to address stress factors. There were noticeable changes in the Perceived Stress Scale (PSS), muscle strength, and could walk without assistance with some difficulty after treatment. The neuropsychiatric perspective incorporating biopsychosocial aspects at the individual level, including consideration of Psychological and Spiritual aspects wherever relevant, is crucial for better outcomes in such cases.